Penerapan Pendidikan Inklusif untuk Anak ADHD - Ulfadhilah, Khairunnisa; Dwi Nurkhafifah, Salsabila (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2025)
This research is qualitative that investigates how to implement inclusive education for children with special needs with ADHD. With this research, it is able to provide references and guidelines for teachers and parents in providing education and stimulation to children who have special advantages in themselves, and the stimulation provided will be more different and more painstaking. This study uses case investigation for data collection such as observations, interviews, and documentation used by PAUD An-Nur. For data analysis including verification and reduction of data presentation data, one of the benefits of this study is to know that the implementation of inclusive education services can run without obstacles with the situation of students who experience special needs.